Work Safety Culture of Latinx Child Farmworkers in North Carolina - Arcury, Thomas A. (Am J Ind Med, 2020)
BACKGROUND: Little research has addressed the safety environment of child farmworkers. This analysis examines the work safety culture experienced by Latinx child farmworkers in North Carolina. METHODS: Survey interviews were conducted in 2017 with 202 Latinx children aged 10 to 17 years employed on North Carolina farms. Analysis included measures of the behavioral, situational, and psychological elements of work safety culture. RESULTS: The work culture on North Carolina farms employing Latinx child farmworkers places limited value on safety. Behaviorally, many did not wear appropriate work clothing (e.g., 47.5% wore gloves, 37.1% wore boots). Situationally, few received safety training for tools (40.6%), machinery (24.3%), or pesticides (26.0%); about one-third (33.7%) had worked piece-rate; and many did not have field sanitation services available (e.g., 37.1% had water for washing, 19.8% had soap). Safety attitudes were mixed, and work safety climate was low, with 21.8% stating that their supervisor was only interested in doing the job fast and cheaply. Greater safety training, field sanitation services, and work safety climate were associated with working in western North Carolina, migrant workers, limited English fluency, and working in tomatoes. Wearing appropriate work clothing, not working piece-rate, fewer unsafe work attitudes were associated with working in eastern North Carolina, seasonal worker, speaking English, and working in tobacco. CONCLUSIONS: This research makes it apparent that efforts are needed to improve safety culture wherever child farmworkers are employed. Current policy is not providing a safe environment for children working on farms in the United States.